The Implementation of Fire Disaster Mitigation at Harris Vertu Hotel Jakarta - Rina Kurniawati; Aji Mahaditia; M.Rizka Galang Y (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This research aims to find out and explain how the Harris Vertu Jakarta hotel is implemented in dealing with disasters that are likely to occur, especially fire disasters, disasters are something that cannot be predicted, and knowing how to deal with disasters is one of the skills that is needed in the hotel industry. because it is an obligation to make hotels safe from the threat of disasters, there are three types of disasters, natural disasters, non-natural disasters, and social disasters. In this research, researchers will conduct research related to non-natural disasters at the Harris Vertu hotel, namely fire disasters. Reseach metods: This study used qualitative-descriptive research techniques that used observation, interviews, and documentation to collect data. The samples of this study is HR Director, Chief Security, and Chief Engineer. Then the results of the data collected will be described descriptively. Result and discussion: The haris Vertu Hotel Jakarta has prepared the staffs to face disasters from the first day the staff worked at the Harris Vertu hotel where on the first day of work they were immediately given a full day of training, usually the training is given by HRD about hotel brands, executive chefs about hygiene, Chief Security about how to respond to disasters. In addition to the training provided on the first working day of the Harris Vertu hotel, it is also routine to conduct training every three months on how to deal with disasters if at any time they occur at the Harris Vertu hotel, things to do when disasters occur and how to use the tools used to deal with disasters.Harris Vertu Hotel also routinely conducts simulations every four months for all its staff, in the simulation each staff is given the opportunity to use all the equipment used to deal with disasters, besides that Hrris Vertu hotel also collaborates with outside parties to carry out this simulation, such as by ambulance, and fire department. Implication: This study focuses to answer the following questions: 1) How does Harris Vertu Hotel prepare for natural disasters, 2) How does Harris Vertu Hotel prepare its staff to face natural disasters. Keywords: Hotel, Fire, Non-natural Disaster, Disaster Mitigation